2018
DOI: 10.1096/fj.201700248rr
|View full text |Cite
|
Sign up to set email alerts
|

Nontypeable Haemophilus influenzae lysates increase heterogeneous nuclear ribonucleoprotein secretion and exosome release in human middle‐ear epithelial cells

Abstract: Nontypeable Haemophilus influenzae (NTHi), one of the most common acute otitis media (OM) pathogens, is postulated to promote middle-ear epithelial remodeling in the progression of OM from acute to chronic. The goal of this study was to examine early quantitative proteomic secretome effects of NTHi lysate exposure in a human middle-ear epithelial cell (HMEEC) line. NTHi lysates were used to stimulate HMEEC, and conditional quantitative stable isotope labeling with amino acids in cell culture of cell secretions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…It has been reported that hnRNP family is required for the packaging into exosomes of a list of mRNAs and noncoding RNAs [17,37,38]. In the current study, hnRNPA1 has been screened out by MS for its up-regulation in gastric tumor tissues.…”
Section: Usp7 Promotes Mir-522 Secretion By Stabilizing Hnrnpa1mentioning
confidence: 93%
“…It has been reported that hnRNP family is required for the packaging into exosomes of a list of mRNAs and noncoding RNAs [17,37,38]. In the current study, hnRNPA1 has been screened out by MS for its up-regulation in gastric tumor tissues.…”
Section: Usp7 Promotes Mir-522 Secretion By Stabilizing Hnrnpa1mentioning
confidence: 93%
“…Cells were maintained in 1:1 of bronchial epithelial cell basal medium (Lonza, Walkersville, MD, USA) and DMEM (Thermo Fisher Scientific) and supplemented with the SingleQuots kit (Lonza) containing bovine pituitary extract, hydrocortisone, human epidermal growth factor, epinephrine, transferrin, insulin, tri-iodothyronine, retinoic acid, gentamycin, and amphotericin-B. We treated the cells with lipopolysaccharide (LPS) at a range of concentrations from 0 to 50 μg/mL and incubated for 24 h. Cells were deprived of SingleQuots 4 h before LPS challenge in bronchial epithelial basal medium/DMEM [11]. We used Western blot to measure the expression of SP-D and NLRP3 in response to different doses of LPS.…”
Section: Methodsmentioning
confidence: 99%
“…Both viral and bacterial agents can cause OM. Nontypeable Haemophilus influenzae (NTHi) is one of the most common infectious pathogens in OM [9-11]. The innate immune response plays a significant role in OM susceptibility in early life before the development of specific immunity [6].…”
Section: Introductionmentioning
confidence: 99%
“…Not unexpectedly, the proteomic analysis showed an enrichment in neutrophil markers and molecules associated with innate immunity, such as immunoglobulins, MUC5B, and heat-shock proteins; also related to neutrophil stimulation were 29 enriched miRNA sequences unique to the middle ear samples, including the most abundant miR-223 [ 45 ]. On the cellular level, it was shown that human middle ear epithelial cells treated with Haemophilus influenzae lysate secrete sEVs containing heterogeneous nuclear ribonucleoproteins, such as hnRNP A2B1 and hnRNP Q, and also miRNAs that might be involved in immunity regulation [ 47 ].…”
Section: Role Of Sevs In Inflammatory Airway Diseasesmentioning
confidence: 99%